Bioclimatic and hydromineral components of natural recreational potential of the Carpathian region of Ukraine - Safranov, Tamerlan; Katerusha, Halyna; Nikipelova, Olena; Katerusha, Olena; Yaraei, Kambiz (Видавництво Львівської політехніки, 2024)
Among the components of the natural recreational potential of the Carpathian region of Ukraine, a special place is occupied by bioclimatic and hydromineral resources, therefore the purpose of the work is to assess their features. The bioclimatic component of the natural recreational potential of this region determines the comfort (discomfort) of human sensations and well-being, so it is important to identify possible positive and negative impacts of various climatic factors and their dynamics in mountain and foothill areas during different seasons of the year. The bioclimatic component of the natural recreational potential is assessed from the point of view of the comfort of climatic conditions for the body of a healthy person. The work is based on the results of modeling the average daily values of air temperature (t), wind speed (v) and relative humidity (f) according to the RCP4.5 scenario (trajectory of changes in the average level of greenhouse gases concentration) from 2021 to 2050 and data from the climate cadastre of Ukraine (1961–1990) at three stations (Dolyna, Rava-Ruska, Uzhgorod) in the foothill areas of the region. There was conducted a study of the possible bioclimatic potential of the Carpathian region of Ukraine and trends of its dynamics until 2050. The article analyzes the features of mineral healing waters of four national nature parks of the Ukrainian Carpathians.
Keywords: bioclimatic conditions; hydromineral resources; mineral waters; natural resources; recreational potential; rehabilitation